A Sulfonozanamivir Analogue Has Potent Anti‐influenza Virus Activity. (15th March 2018) - Hadházi, Ádám; Li, Linghui; Bailly, Benjamin; Maggioni, Andrea; Martin, Gael; Dirr, Larissa; Dyason, Jeffrey C.; Thomson, Robin J.; Gao, George F.; Borbás, Anikó; Ve, Thomas; Pascolutti, Mauro; et al.
Abstract: Influenza virus infection continues to cause significant, often severe, respiratory illness worldwide. A validated target for the development of anti‐influenza agents is the virus surface protein sialidase. In the current study, we have discovered a highly potent inhibitor of influenza virus sialidase, based on a novel sialosyl sulfonate template. The synthesised 3‐guanidino sialosyl α‐sulfonate, a sulfonozanamivir analogue, inhibits viral replication in vitro at the nanomolar level, comparable to that of the anti‐influenza drug zanamivir. Using protein X‐ray crystallography we show that the sialosyl α‐sulfonate template binds within the sialidase active site in a 1 C 4 chair conformation. The C1‐sulfonate moiety forms crucial and strong‐binding interactions with the active site's triarginyl cluster, while the 3‐guanidino moiety interacts significantly with conserved active site residues. This sulfonozanamivir analogue provides a new direction in anti‐influenza virus drug development. Abstract : Structural in flu ence : A highly potent influenza virus sialidase inhibitor was developed based on a novel sialosyl sulfonate template. An X‐ray crystallographic study shows that substituents of the sulfonozanamivir analogue interact with key conserved residues of the influenza virus sialidase active site, leading to nanomolar‐level inhibition of both sialidase activity and viral replication.